Ecoturismo e interpretação ambiental como estratégia de divulgação do patrimônio natural e cultural de Roque Gonzales-RS - Anschau, Magali Rambo (2016)
Touristic activities capable of highlighting the experiences and knowledge of natural and/or cultural characteristics should be included in tourism planning, enabling the development of important values for society. The landscape has elements of both natural and cultural expression, known as natural heritage and cultural heritage, which are seen as elements to be preserved for future generations. The natural heritage concerns the basis of memory by recording the past, which is essential for the establishment of cultural heritage.Comprehending what becomes significant in the landscape is understood as environmental interpretation and aims at the reading of natural and cultural heritage. Environmental interpretation is regarded as an interpretive treatment, which presses for the visitor's involvement with what is being interpreted. In this context, this study focused on the use of the touristic potential of the natural and cultural heritage of Roque Gonzales, whilst using interpretative instruments as a dissemination strategy of natural and cultural heritage. The municipality of Roque Gonzales is located in the northwest portion of the state of Rio Grande do Sul, in the missionary region. The proposed goal aimed to survey the natural and cultural heritage of Roque Gonzales. Based on this information, an interpretive plan for the sites of patrimonial relevance was conducted, thus collecting data on the existing infrastructure in the city and presenting a management statement for the sites of patrimonial relevance. In this way, we surveyed nine sites of heritage interest among the natural and cultural heritage sites: the Casa de Memoria (in restoration), Prainha (under construction), the Salto Pirapó, the Cordilheiras da Esquina Emanuel, Cerro Inhacurutum, the Cerro Inhacurutum lookout, Assunção do Ijuí, the Cruz de João de Castilho and the Cotovelo do rio Ijuí. In the Casa de Memória and Prainha, intervention is being carried out by Eletrosul and the municipality of Roque Gonzales, of which an analysis is being made of what is being proposed by the respective agencies. In the other heritage sites of interest, interpretive tools were proposed for the natural and cultural heritage according to the survey carried out. In addition to the survey of the necessary infrastructure for tourism development, a proposal for a tour guide for the municipality of Roque Gonzales was presented.In this sense , understand the dynamics and the meanings of the natural and cultural heritage of Roque Gonzales through environmental interpretation is critical to the dissemination and subsequent exploitation of this heritage process. In addition , this study extends the discussion of the relationship between society and nature through the promotion of natural and cultural heritage through interpretative instruments and ecotourism practices.